Albuminuria diagnosis in patients over 55 years of a care network - Figueroa-Montes, Luis Edgardo (2014)
Objective. To determine the diagnosis of albuminuria (microalbuminuria, macroalbuminuria) in patients over 55 years of Rebagliati Care Network (RCN) using the albumin/creatinine ratio (A/CR). Materials and methods. We performed a cross-sectional, descriptive during 2012, in adults over 55 years of RAR, of both sexes, who have conducted tests on urine albumin and creatinine. We used the ratio A/CR for the assessment of albuminuria (microalbuminuria, macroalbuminuria). Results. The study involved 3943 patients. The median age was 70 ± 8,96 years and 57,10 % (N = 2250) were women. The 23 % (N = 918) of patients had albuminuria, 17,92 % N = 706) microalbuminuria and 5,38 % (N = 212) macroalbuminuria. The Hospital III Suárez Angamos had the highest percentage of patients with albuminuria. When evaluating the strength of Kappa between urinary albumin method versus the ratio A/CR observe a substantial concordance (k = 0,789) between these diagnostic methods. Conclusions. The 23,30 % of patients over 55 years of RCN, presented albuminuria. A total of 212 (5,68 %) patients had macroalbuminuria. A therapeutic intervention for these patients with microalbuminuria or macroalbuminuria, effectively decrease the increase of chronic kidney disease in the RCN.